Identifying Critical Climate Periods for Vegetation Growth in the Northern Hemisphere. Issue 8 (25th August 2018) - Chen, Chen; He, Bin; Guo, Lanlan; Zhang, Yafeng; Xie, Xiaoming; Chen, Ziyue
Abstract: Vegetation‐climate relationships have been extensively investigated in previous studies, yet the critical seasons and corresponding climate factors influencing annual vegetation growth in a changing climate remain unclear. Relying on Global Inventory Modeling and Mapping Studies NDVI3g data and climate data from 1982 to 2013, this study explored the responses of vegetation growth to climate changes in the Northern Hemisphere (NH), with an emphasis on vegetation changes and legacy effects during different seasons. We further identified the most critical season in terms of vegetation growth. We found an apparent seasonal shift in the influence of climate change on vegetation growth in the NH. In addition, we observed legacy effects of climate change on vegetation growth throughout the seasons. Winter temperatures exerted a positive impact on vegetation growth during the following spring in Europe and central North America. Spring precipitation was an important factor for summer vegetation growth in dry areas. Using partial least squares regression, the relative importance of seasonal climatic factors on annual vegetation growth conditions were determined. This study finds that the vegetation in more than 40% of the NH is controlled by temperature, especially spring temperatures (12.8%). Precipitation and solar radiation were the dominant climate factors influencing vegetation growth in 29.9% and 29.1% of vegetated regions, respectively. Furthermore, compared with the period from 1983 to 1997, the influence of seasonal solar radiation on vegetation growth increased in the NH during the period from 1998 to 2013. This phenomenon was accompanied by reductions in the influence of spring and summer temperatures. Key Points: We observed seasonal differences in the effects of climate changes on vegetation growth in the Northern Hemisphere, as well as legacy effects Vegetation growth in over 40% of the Northern Hemisphere was influenced by temperature, especially spring temperature (12.8%) In recent years, the influence of spring and summer temperatures on vegetation have decreased, while that of seasonal solar radiation has increased